Дослідження питань використання сучасного мультимедіа при рішенні проблем ергодизайну - Асонов, В. І.; Степаненко, О. Г. (My University, 2020)
With the development of technical capabilities of materials processing appeared a considerable number of household items, the form of which was created taking into account anthropometric and anatomical data of a person and meeting the requirements of convenience and psychological comfort.
Keywords: мультимедіа